IMPLEMENTASI UU NO 32 TAHUN 1974 TENTANG PERANAN LURAH DALAM MELAKSANAKAN SYSTEM PEMERINTAH DESA YANG BAIK DAN BERDAYA GUNA DI KABUPATEN MAHAKAM ULU KEC.LONG PAHANGAI - Dewi Novianti Nst (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTStudies uu No. 32 tahun 1974 about the role lurah undertaking system village governane in order to effectively and efficiently guna di Mahakam ulu subdistrict regency long Pahangai under the guidance of Mr.DR.Abdul Munif,SH,M.Hum as a supervisor I and DR. Derawan Hasyim,M.Si as supervisor II.            Objective to obtain concrete data relating to the issues discussed and to know the efforts made and to find answers to problems that have been formulated and to prove or test the hypotheses of the study and to vaildate the hypotheses that have been put forward.            Conclusions drawn from the reseacrh is that rural communities can participate in the development didesanya the efforts should be made is the following, among others:The role of the village headman in the government system as followes:Lurah as the community to set priorities,pay attention to public opinion as it also has responsibility to the people of his village, the local governments and the central gobernment.Lurah has a very large role, especially in the construction of the village.Lurah role that is able to develop religious values and customs in the village in order to create a safe community, peaceful and democratic.Lurah play its role in accordance with exisiting legislation and encourages the development of new values which are positive for the community and encourage community participation towards independence.